Illocutionary Speech Act Of Sellers And Buyers At Tomang Market West Jakarta - Apri Permana (PIKTORIAL : Journal of Humanities, 2021)
The aim of the study was to describe the type and function of the communication of the sell-er with the buyer in the west Jakarta stock exchange. The study uses qualitative descriptive methods. Data collection using the attendees and notebooks. As for the conversation taken by the seller with the seller at the Jakarta stock exchange: The vendors speech with the chicken claw buyer, the vendors speech with the kitchen knife, and the speakers speech in the gamis coat. After data has been collected and classified according to research questions, the data is further analyzed using the routed speech theory as searle. Studies have obtained 24 data containing acts of speech. Lokusi speech has been found in as many as 6 speech, in which question speech amounts to 3 speech, and speech to 3 speech. As more than 12 words are found, as 3 words are said, directives speech as much as 3 speech, commission literacys 3 speech, and expressie syllables amount to 3 speech. Immigra-tions speech was found as many as 6 words, in which verbal amount to 3 speech, and verbal nonverbal speech to 3 speech. Whereas the function of speech that is found within the seller with buyer at the west Jakarta Tomang market is very vary. The are question transitions that serve to ask question and statement assesssments that work to make a statement. As a result of obtive speech there is a useful astive syllable that serves to inform, a directive illegality that serves for solictation, a functioning commission of liability and offer, and an expressive illegality that works for complaints and sadness. The speech of others includes verbal speech that works for notification and nonverbal speech that works for speaking with the package, shaking your head, and smiling.